The Pivitol Role of Perceived Discretion in Top Teams Setting a Research Agenda. - Galavan, Robert; Kakabadse, Andrew P.; Korac-Kakabadse, Nada (Cranfield University, 2003)
The strategic leadership research stream characterisd by the predominantly instrumental upper-echelon research stream has provided extensive support for the strategic choice school of thought. In recent years it has been ctiticised for failing to develop from an exploration of whether relationships exist between managers background characteristics and their strategic choices and firm performances to an exploration of how managers characteristics influence outcomes. This paper provides a way forward and identifies perceived discretion as a pivotal concept in the exploration of the black box of demographic research and clearly separates the concepts of perceived, situational and enacted discretion. A broad conceptual framework, built on rather than replacing precious frameworks, is presented and future research is indicated. The concept of the discretion funnel is also introduced.
Keywords: Perceived discretion; upper-echelons theory; top teams; strategic leadership; leadership demographics; cognitive structure; enacted discretion; belief system